Equilibrium and thermodynamic parameters of single and binary mixture biosorption of lead(II) and copper(II) ions onto Pseudomonas putida - Uslu, Gulsad; Tanyol, Mehtap (Elsevier Science Bv, 2006)
The biosorption of lead (11) and copper (H) ions, single component and binary systems. by dried P putida was investigated in a batch system. The effects of initial pH, temperature. initial single and binary mixture concentrations on the biosorption kinetics and equilibrium uptake of each component, both single and binary mixtures were investigated. The bacteria] biomass exhibited the highest single and binary lead (11) and copper (11) ions uptake capacity at 25 and 30 degrees C. respectively. the initial pH value of 5.5 and at the initial metal ions concentration of 100 mg dm(-3). The Freundlich and Langmuir adsorption models were used for the mathematical description of the biosorption equilibrium and isotherm constants were evaluated at different temperatures. Adsorption data were well described by the Langmuir model. although they could be modeled by the Freundlich equation. The thermodynamics constants of the adsorption process: Delta H degrees. AS degrees and AG degrees were evaluated. The results showed that biosorption of single and binary lead (11) ions on P. putida were exothermic and spontaneous. While biosorption of single and binary copper (11) ions on P putida was endothermic and spontaneous. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: P. putida; biosorption; single and binary lead (II)-copper (II) ions; isotherms; thermodynamics